The Influence of Job Stress and Job Satisfaction on Driver Performance - Mustofa, Muhammad Bisri; Musprihadi, Ribut (Faculty of Economics and Business UNTAG Semarang, 2024)
Several previous studies on the influence of job stress and job satisfaction on performance is still inconsistent This study aims to determine the effect of job stress and job satisfaction on driver performance. The sample in this study was 96 Grab motorbike drivers in the Semarang. The data analysis technique used is multiple linear regression. The results show that job stress has a negative effect on driver performance, while job satisfaction has a positive impact on driver performance. The conclusion states that the higher the job stress the driver feels, the significantly lower his performance. Furthermore, the higher the driver's job satisfaction level, the more his performance.